The Role of Transformational Leadership on Firm Performance: Mediating Effect of Corporate Sustainability and Moderating Effect of Knowledge-Sharing - Shahzad, Muhammad Asim; Iqbal, Tahir; Jan, Naveed; Zahid, Muhammad (Frontiers in Psychology, 2022)
The primary purpose of the research is to investigate the mediating role of corporate sustainability in the relationship between the impacts of transformational leadership on the performance of firms. This study also aimed to investigate the moderating role of knowledge-sharing on the relationship of transformational leadership with corporate sustainability. Respondents of the study were the top management of large Chinese automobile sectors, such as Shanghai Automotive Business Corporation (Group), China FAW Group Corporation, Dongfeng Motor Co., Ltd., Beijing Automotive Group Co., Ltd., and China North Industries Group Corporation. These are the companies with the biggest market share in the automobile manufacturing industry in China. The data was gathered by using a self-administrative survey questionnaire from 198 individuals operating in different automobile industries in different sectors of China. The data were analyzed using structural equation modeling (SEM) through the Smart PLS 3.3.2 software. The results of this study revealed that transformational leadership has a positive and significant effect on the performance of the firm. Corporate sustainability has a significant positive mediating role in the association of transformational leadership and firm performance. Findings indicated that knowledge-sharing also has a positive moderating role in the association between transformational leadership and firm performance. The findings of this study contribute to the body of knowledge and show that leadership style has a significant effect on firm performance and that knowledge-sharing culture in firms is essential for better performance of the firm. Furthermore, firms may improve their performance by improving their sustainability and by creating knowledge-sharing culture. The findings are important, particularly in connection with a developed country like China. The findings have important insights for various stakeholders, i.e., government, regulatory bodies, practitioners, academia, industry, and researchers.